"A Place for Everybody": Students' Perspectives on Inclusive Behavior in School. (August 2022) - Siperstein, Gary N.; Ballard, Staci C.; Jacobs, Holly E.; Rodriquez, Jason; Shriver, Timothy P.
Understanding students' perspectives on inclusive behavior is important for addressing the bullying, victimization, and exclusion that many middle school and high school students, particularly marginalized students, continue to face at school. This study explored how students give meaning to inclusive behavior at school and the conditions that support inclusive behavior. Using data from 30 focus groups conducted with students, the findings expand on three primary themes: students' broad descriptions of inclusive behavior, their understanding of the qualities and characteristics of an inclusive person, and their beliefs about what makes a school inclusive. Findings from this study can inform organizational practices to facilitate inclusive behavior in schools in a manner consistent with how students themselves view inclusivity.